Intermittent hypobaric hypoxia induces oxidative stress and vascular remodeling in rat pulmonary arteries - Sri Nurbowo Ardi; Muhammad Arza Putra; Dewi Sukmawati; Puspita Eka Wuyung; Wawan Mulyawan; Wardaya; Wiwien Heru Wiyono (Jurnal Medik Veteriner, 2026)
Flight crews frequently experience intermittent hypobaric hypoxia (IHH), which may trigger oxidative stress and vascular remodeling in the pulmonary arteries. This study investigated the effects of IHH exposure on oxidative stress markers, tunica media thickness, and the expression of LR11 and HIF-1α proteins in rat pulmonary arteries using five groups of healthy male Sprague–Dawley rats (n = 5 per group). Twenty-five male Sprague–Dawley rats were divided into five groups: a control group and four treatment groups exposed to simulated altitudes of 25,000 ft (7,620 m) for 5 minutes per day over 1, 3, 7, or 14 days. Levels of HIF-1α and LR11 were measured using ELISA, oxidative stress markers such as γ-glutamyl-cysteinyl-glycine (GSH) and malondialdehyde (MDA) were analyzed spectrophotometrically, and tunica media thickness was assessed histologically. HIF-1α levels peaked after acute hypoxia exposure and declined with prolonged exposure, whereas LR11 levels progressively increased, peaking in the 14-day group. MDA levels, reflecting oxidative stress, were highest after 3 days of exposure, while GSH levels decreased in all hypoxia groups compared with the control. Histological analysis showed the greatest tunica media thickness in the 3-day exposure group, followed by gradual reductions. Although no statistically significant correlations were found between protein levels and tunica media thickness, similar directional trends suggest biologically relevant associations. Intermittent hypobaric hypoxia (IHH) induces dynamic changes in oxidative stress and vascular remodeling in rat pulmonary arteries. Acute hypoxia increases HIF-1α expression and oxidative stress, whereas repeated exposures appear to trigger compensatory adaptations, including LR11 upregulation and tunica media remodeling. These findings demonstrate measurable molecular and structural alterations underlying pulmonary vascular responses to repeated high-altitude exposure.